The Effect of Type and Concentration of Receiving Phase on Silver Separation Efficiency by Supported Liquid Membrane Technique - Kurniasih, Yeti; Basri, Hasan; Nufida, Baiq Asma (Jurnal Ilmiah Mandala Education (JIME), 2024)
The Effect of The Type and Concentration of The Receiving Phase on The Efficiency Of Silver Separation with Liquid Supported Membrane Techniques. The process of making negative x-ray films in a radiology laboratory produces liquid wastes containing various chemical compounds with the main content being Ag metal (in the form of Ag+ cations). This waste is categorized as a dangerous and toxic material. Therefore it is necessary to separate the Ag metal before it is discharged into the environment so as not to be harmful to life and the environment. One of the separation techniques that can be used is with supported fluid membrane technique (Supported Liquid Membrane, SLM). The supported liquid membrane has three important components: the feed phase containing the component to be separated, the membrane phase containing the carrier compound and the receiving phase containing the integral component. The three-phase composition determines the efficiency of the separation process. This study aims to identify the type and concentration of the receiving phase solution to improve silice metal separation efficiency by SLM technique. To obtain an efficient composition in the recipient phase was carried out by varying the type of acid received solution ie H3PO4, HNO3 and CH3COOH with respective concentrations of 0.01; 0.05; 0.10; 0.15; and 0.20 M. Measurement of metal ion concentration of Ag+ before and after transport was determined by Atomic Absorption Spectrophotometer (SSA) at wavelength 328,22 nm. Based on the result of research that type and concentration of acid solution in the receiving phase has an effected on separation efficiency. The optimum transport percentage has obtained on the used of H3PO4 receptor solution at a concentration of 0.1 M with a percentage of Transport Ag of 46.84%.